2000
DOI: 10.1002/1097-4687(200008)245:2<110::aid-jmor3>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural observations on sperm storage in the ovary of the platyfish, Xiphophorus maculatus (Teleostei: Poeciliidae): The role of the duct epithelium

Abstract: Sperm storage is an important phenomenon occurring in viviparous and oviparous teleosts and contributes to the reproductive life history of these forms. There is a paucity of morphological studies on sperm storage in fishes. The majority of these have been confined to the light level of investigation. In this report, we describe, at the ultrastructural level, sperm storage in the viviparous platyfish, Xiphophorus maculatus. Female platyfish, as is typical of the poeciliids, are capable of storing viable sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…After release into the female genital tract, sperm can be stored alive for months before fertilization of mature oocytes [33], and these females may produce 4-5 broods after a single insemination [39]. These features make sperm cryopreservation and fertilization trials with cryopreserved sperm far more difficult in Xiphophorus than in those species that utilize external fertilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After release into the female genital tract, sperm can be stored alive for months before fertilization of mature oocytes [33], and these females may produce 4-5 broods after a single insemination [39]. These features make sperm cryopreservation and fertilization trials with cryopreserved sperm far more difficult in Xiphophorus than in those species that utilize external fertilization.…”
mentioning
confidence: 99%
“…However, sperm from Xiphophorus fishes with internal fertilization are in many ways more like the sperm of mammals, in which motility and fertility are necessary within the female reproductive tract. Additionally, sperm of Xiphophorus fishes are maintained in the female and fertilization can occur for several months after mating [32,33,38].…”
mentioning
confidence: 99%
“…12 Most of these studies were performed with X. hellerii and X. maculatus, and the major findings were: 1) females can store sperm in folds of the oviduct for months and produce 3-5 broods from a single mating even in the absence of a male; 25,30 2) females may reach sexual maturity within 4-6 months; however, maturity is governed by specific genes, 29 and may be influenced by other factors such as social behavior 31 and body size; 32 3) embryonic development from fertilization to birth is about 22 days; 25 4) the time intervals between the first few broods in females can be irregular and vary between 26 and 90 days, although the tendency is to cycle at about 28 days with mature females, consistent maintenance, and a conducive environment. Based on these observations, appropriate approaches for increasing artificial insemination success rates of Xiphophorus females may include:…”
Section: Possible Approaches For Increasing Offspring Production Effimentioning
confidence: 99%
“…Sufficient Xiphophorus sperm can be stored for months in folds of the oviduct to fertilize as many as four or more broods. 25,30,39 Given the viability of stored sperm, fertilization could occur whenever oocytes are mature and ovulated. It is currently difficult to estimate the stage of ova development within females.…”
Section: Figmentioning
confidence: 99%
“…One study in X. maculatus showed that sperm stored in inseminated females became associated with specific epithelial cells lining the oviduct in two forms: 1) sperm were stored within deep surface pits or pockets, and 2) sperm were taken up and incorporated within the cytoplasm of specific epithelial cells. These epithelial cells play an undefined role in sperm storage and could be associated with secretory or nutritive support of sperm [20]. Further investigation is necessary to evaluate such FIG.…”
Section: Immobilized and Nonimmobilized Sperm In Cryopreservation Andmentioning
confidence: 99%